2016
DOI: 10.4103/2231-0762.195519
|View full text |Cite
|
Sign up to set email alerts
|

Pain and distress induced by elastomeric and spring separators in patients undergoing orthodontic treatment

Abstract: Aims and Objectives:The objective of the present investigation is to evaluate patients’ pain perception and discomfort, the duration of pain and the level of self-medication over time during tooth separation, and the effectiveness of elastomeric and spring types of orthodontic separators in Saudi population.Materials and Methods:The study group consisted of 30 female adolescent patients who had elastomeric/spring separators as part of their orthodontic treatment. A self-administrated questionnaire comprising 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
6
1
2
Order By: Relevance
“…The amount of pain was found to be greater during the first 24 hours of separator placement, similar to previous studies. 9 , 12 , 24 , 25 The intragroup comparison revealed that the pain with elastomeric separator was so intense at the time of placement that the pain reduction on each day, for the entire research period, was statistically significant. On the other hand, Kesling and Kansal separators showed significant pain reduction only until day 3, which means that lesser residual pain persists after the third day of placement, leading to better patient comfort.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The amount of pain was found to be greater during the first 24 hours of separator placement, similar to previous studies. 9 , 12 , 24 , 25 The intragroup comparison revealed that the pain with elastomeric separator was so intense at the time of placement that the pain reduction on each day, for the entire research period, was statistically significant. On the other hand, Kesling and Kansal separators showed significant pain reduction only until day 3, which means that lesser residual pain persists after the third day of placement, leading to better patient comfort.…”
Section: Discussionmentioning
confidence: 97%
“…The placement of separators causes pressure, tension, soreness and pain, which can be detrimental to the patient’s attitude towards further orthodontic procedures. 10 - 12 The separator-associated pain also interferes with functions like chewing or dietary pattern, leading to discomfort and need for medication. A subjective method for pain assessment is the Visual Analogue Scale (VAS), which has been extensively used in various studies for assessment of pain intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is believed by Banerjee et al (2018) that the patients' circulatory system could be regulated effectively to promote their heart rate to be normal through parasympathetic excitation and sympathetic suppression. It is believed in the study of Al-Balbeesi et al (2016) that there would demonstrate certain difference in the clinical manifestations of pain after placing the bow wire in orthodontic treatment for patients with temporomandibular joint disorder syndrome, and appropriate orthodontic force control could improve the pain effect effectively. Besides, Minghui et al (2017) further proposed that there was no difference in the degree of periodontal pain after placing the first two bow wires, but the duration of pain after placing the second bow wire was shorter, during orthodontic treatment.…”
Section: Improvement Of Vas Pain Symptoms Of Patients In the Two Groups Before/after Nursingmentioning
confidence: 99%
“…Diversos estudos sugerem que a dor provocada pelos separadores elastoméricos se inicie quatro horas após a instalação e alcance o pico de forma gradual nas primeiras 24 horas. A redução da sensação dolorosa pode começar por volta das 72 horas após a instalação, quando se iniciam os processos de reparo tecidual, normalizando após cinco ou sete dias 1,3,5,6,20,22,23 .…”
Section: Revisão De Literaturaunclassified
“…Quando separadores elastoméricos são inseridos nos espaços interdentais, inicia-se uma cascata de eventos inflamatórios que resultam em respostas teciduais com liberação de mediadores inflamatórios associados a dor. O aumento de prostaglandina E2 tem sido associado à dor inicial e o aumento de interleucina-1 tem sido associado ao pico de dor em 24 horas após a colocação dos separadores elastoméricos 5,6 .…”
Section: Introductionunclassified